Mortality associated with passive smoking in Hong Kong (BMJ Publishing Group, 2005)

(untitled)
Passive smoking can cause death from lung cancer and coronary heart disease, but there is little evidence for associations with other causes of death in never smokers. A recent study showed increased all cause mortality with exposure to secondhand smoke at home but did not examine associations with specific causes of death and dose-response relations.1We have published estimates of the mortality attributable to active smoking in Hong Kong2 and now present the related findings on passive smoking at home.